Analisis Daya Dukung untuk Mendukung Swasembada Pangan di Provinsi Kalimantan Utara - Patria Kusumadiya (Journal of Environmental Engineering and Waste Management, 2023)
Abstract. Population growth, regional development, and inaccuracy in planning targets will impact and disrupt food self-sufficiency Objectives: Analyzing and evaluating Carrying Capacity (CC), Assessing and analyzing land requirements in North Kalimantan Province Method and results: The research method is qualitative, which is analyzed descriptively quantitative. The formula of CC developed from a combined concept of the theory of Odum, Cristeiler, E Howard, and Issard. The results showed that the food carrying capacity of North Kalimantan Province in 2020 was 0.56 and land requirements for paddy 26.912 ha. Food carrying capacity is projected to decline to 0.28, and land requirements for paddy will increase to 38.479 ha in 2037. Conclusion: North Kalimantan Province's Food carrying capacity was incapable of food self-sufficiency (Class III) and continues to decline from 2016-2020 until projected in 2037. Added paddy-harvested area or land in 2037 is needed to realize food self-sufficiency through an alternative policy of expanding paddy fields (extensification) by maintaining productivity stability or increasing productivity (intensification).